2020
DOI: 10.1002/app.49602
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid and high‐density polyethylene blend: Characterization and application in additive manufacturing

Abstract: This research reports a novel polylactic acid (PLA) blend with high density polyethylene (HDPE) and polyethylene graft maleic anhydride (PE‐g‐MAH) to mitigate the PLA degradation issues associated with high temperatures, soil and water exposure. The blend was prepared with a melt blending process and directly printed with a custom‐built pellet printer to maintain the “as prepared” properties. Thermal stability was analyzed in terms of mechanical strength at different bed temperatures and postprinting aging for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 71 publications
(101 reference statements)
1
26
0
Order By: Relevance
“…PLA/HDPE compatibilized with PE-g-MA showed better ductility and resistance to moisture degradation than pure PLA. 13 PLA/HDPE compatibilized with ethylene-butyl acrylateglycidyl and with fibers exhibited improved thermal stability and tensile strength and reduced impact resistance. 14 Techniques that do not use compatibilizers for the manufacture of these mixtures have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…PLA/HDPE compatibilized with PE-g-MA showed better ductility and resistance to moisture degradation than pure PLA. 13 PLA/HDPE compatibilized with ethylene-butyl acrylateglycidyl and with fibers exhibited improved thermal stability and tensile strength and reduced impact resistance. 14 Techniques that do not use compatibilizers for the manufacture of these mixtures have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Particular to the mechanical strength, the tensile strength for PLA (55 MPa) is high as compared to ≈41 MPa of ABS, ≈45 MPa for polycarbonate (PC), ≈38 MPa for ABS/PC, ≈35 MPa for Nylon, ≈38 MPa for polypropylene (PP) [ 3 ]. However, as being a polyester, the backbone of PLA main chain is vulnerable to chemical scission due to poor thermal stability [ 11 , 12 ]. The recent work from the authors of this research has found visible degradation of C-O-C and C=O groups from Fourier transform infrared spectroscopy (FTIR) analysis due to thermal aging [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as being a polyester, the backbone of PLA main chain is vulnerable to chemical scission due to poor thermal stability [ 11 , 12 ]. The recent work from the authors of this research has found visible degradation of C-O-C and C=O groups from Fourier transform infrared spectroscopy (FTIR) analysis due to thermal aging [ 12 ]. This kind of structural deficiency can cause detrimental effects in large-scale AM applications aimed for real environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations